Stent location and effectiveness in different types of iliac vein compression - XUE Song, YAN Dong, SHI Huihua, ZHAO Zhen, LU Xinwu, YIN Minyi (Waike lilun yu shijian)
Objective To investigate the stent location and effectiveness in different types of iliac vein compression.Methods A retrospective analysis was conducted on patients with left iliac vein compression who underwent stent implantation at our department from June 2021 to December 2023. Based on the location of compression, patients were categorized into high, classical, and low types. The patients’ general information, lesion characteristics, stent details, stent patency, and clinical outcomes were analyzed and followed up.Results A total of 242 patients were included in this study. And 90. 9% (220 cases) were the classical type, 5.4% (13 cases) were the high type, and 3.7% (9 cases) were the low type. There was no significant difference in age distribution, gender ratio and comorbidities among the three groups. The length of inferior vena cava protruding from the high type was significantly longer than that of the classical type[(3.1±0.8) cm vs. (1.6±1.0) cm, P<0.001), but significantly shorter in the low type[(-0.7±2.4) cm vs. (1.6±1.0) cm, P<0.001). The mean follow-up time was (18.0±7.0) months. The stent patency rate was 97.0% at 1 year and 92.8% at 2 years postoperation. The clinical symptoms of the three groups were significantly relieved. No thrombosis was found in right limbs.Conclusions There is a significant difference in the location of the stent tip between classical and non-classical compression types. Complete coverage of lesion by the stent should be the prerequisite for stent placement in treatment of all three types. Small sample, short-term follow-up data suggested that stents can also relieve clinical symptoms and have good patency rate in the high compression type and the low compression type.